Rekrutmen dan Penempatan Karyawan di Sekolah Islamic Az-Zakiyah Medan - Aditya Ramadhan; Fiky Maulana (Universitas Palangka Raya, 2025)
Recruitment and employee placement are vital aspects of human resource management that play a strategic role in achieving an organization's vision and mission, including at Islamic Az-Zakiyah School in Medan. This school aims to produce a generation that is morally upright, intelligent, and competitive in the global era. This study aims to understand the recruitment and placement processes at the school, including the challenges and strategies employed to ensure a workforce qualified for Islamic educational standards. This qualitative descriptive study utilized interviews, observations, and document analysis. The results revealed that recruitment involves administrative screening, written tests, interviews, and micro-teaching, while employee placement is based on competencies and school needs. The findings also highlight challenges in meeting ideal human resource qualifications, addressed through collaboration with educational institutions and continuous employee training. The study concludes that structured recruitment and placement processes, along with comprehensive employee development programs, have enabled Islamic Az-Zakiyah School to create a high-quality educational environment rooted in Islamic values.